2016
DOI: 10.2139/ssrn.2727130
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Effects of 2007 Family Policy Changes on Probability of Second and Subsequent Births in Russia

Abstract: Estimating effects of 2007 family policy changes on probability of second and subsequent births in Russia 4From 2007 to 2014 total fertility rate in Russia increased from 1.42 to 1.75. To what extent this growth is related to a package of family policy measures introduced in 2007? Although the maternity (family) capital program is the most well-known innovation of the 2007 reform, we argue that the new rules of monthly childcare allowance assignment is its another major component. Since all measures were intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In East Asia, future fertility will be affected by change (or its lack) in its rigid labour markets and its strongly unbalanced gender relations. In Eastern Europe, cohort fertility trends partly depend on the effectiveness of pro-natalist measures implemented particularly by the Belarusian, Russian, and Ukrainian governments in the 2000s, which targeted especially second and third births, and which have had a mixed effect so far (for Russia, see Frejka and Zakharov 2013;Biryukova, Sinyavskaya, and Nurimanova 2016). In the German-speaking countries, especially Austria and Germany, more flexible parental leave schemes and the expansion of early childcare provision may help to achieve a modest upturn in cohort fertility, possibly even heralding a decline in childlessness in the region.…”
Section: Discussion: the Regional Context Of Cohort Fertility Declinesmentioning
confidence: 99%
“…In East Asia, future fertility will be affected by change (or its lack) in its rigid labour markets and its strongly unbalanced gender relations. In Eastern Europe, cohort fertility trends partly depend on the effectiveness of pro-natalist measures implemented particularly by the Belarusian, Russian, and Ukrainian governments in the 2000s, which targeted especially second and third births, and which have had a mixed effect so far (for Russia, see Frejka and Zakharov 2013;Biryukova, Sinyavskaya, and Nurimanova 2016). In the German-speaking countries, especially Austria and Germany, more flexible parental leave schemes and the expansion of early childcare provision may help to achieve a modest upturn in cohort fertility, possibly even heralding a decline in childlessness in the region.…”
Section: Discussion: the Regional Context Of Cohort Fertility Declinesmentioning
confidence: 99%
“…For more information about the project and publications, see: http://www.socpol.ru/research_projects/proj12.shtml. 6 WWW.DEMREVIEW.HSE.RU Our findings, based on an analysis of "macro-demographic" and "macro-sociological" data, have received support from researchers who analyse current trends in fertility in Russia using econometric methods based on microdata of surveys [Chirkova 2013;Slonimczyk, Yurko 2015;Biryukova, Sinyavskaya, Nurimanova 2016]. These and certain other studies have shown that the effect of the maternity capital programme and other measures enacted in 2007 on the reproductive behaviour of Russians, although positive, is quite weak 4 .…”
Section: Introductionmentioning
confidence: 72%
“…Maleva and others [7]; А.О. Tyndik [8]; S. Biryukova and others [9]), as well as the works of foreign researchers: F. Slonimczyk, A.V. Yurko [10].…”
Section: A Results Of Theoretical Researchesmentioning
confidence: 99%